A seduction at Christmas - Maxwell, Cathy (Maxwell, Cathy. Scandals and seduction., 2008)
Desperate and poverty-stricken, Fiona Lachlan reluctantly agrees to a plan to lure the notorious Duke of Holburn into trouble, but when the plot goes wrong, she finds herself posing as his ward and trying to help him avoid the killers on his trail.